A group of species "Psychropotes longicauda" (Psychropotidae, Elasipodida, Holothuroidea) from the Kuril-Kamchatka Trench area (North-West Pacific). (January 2020) - Gebruk, Andrey V.; Kremenetskaia, Antonina; Rouse, Greg W.
Highlights: Psychropotes longicauda is re-described, its two varieties, P. longicauda var. monstrosa and P. longicauda var. fuscopurpurea, are assigned to separate species. The three species, P. raripes, P. dubiosa and P. dyscrita, are re-established. Two species from abyssal and hadal depths in the Kurile-Kamchatka Trench area are described as new to science. The species P. longicauda for long time thought to be cosmopolitan appeared to be a complex of at least eight separate species. Abstract: Collections of holothurians taken in 2012–2016 by three German-Russian deep-sea expeditions to the Kuril-Kamchatka Trench area (KuramBio, SokhoBio and KuramBio II) were examined. Here we present data on the genus Psychropotes (Psychropotidae, Elasipodida). Based on new material and some additional (mainly old) material from the North-West and East Pacific, we re-describe the species Psychropotes longicauda Théel, 1882, describe two varieties, P. longicauda var. monstrosa Théel, 1882 and P. longicauda var. fuscopurpurea Théel, 1882, as separate species, re-establish the species P. raripes Ludwig, 1893, P. dubiosa Ludwig, 1893 and P. dyscrita (Clark, 1920), and describe two new species: P. moskalevi sp. nov. and P. pawsoni sp. nov.